Multi‐period probabilistic‐scenario risk assessment of power system in wind power uncertain environment. Issue 2 (1st February 2016) - Deng, Weisi; Ding, Hongfa; Zhang, Buhan; Lin, XiangNing; Bie, Pei; Wu, Jiasi
Abstract : With the wind generation increasingly penetrating the power grids, there is a growing interest in developing new risk‐based assessments for the grids security analysis. This study develops one kind of such risk tools to evaluate the security risks of power grids under certain amount of wind generation in a short period of time. First of all, a very short‐term uncertainty model of wind generation is introduced. Then the conditional value‐at‐risk is used to design a safety distance (S‐D), revealing the tail risks of operating states. Based on S‐D, four new indices are defined to highlight the risks in a near future with considerable change of wind power output. The overall security assessment tool is compared with the conventional method both on a benchmark test system and a real power system in China. The results demonstrate the effectiveness and some advantages of this new risk‐based tool.